Supplementing Mannan Oligosaccharide Reduces the Passive Transfer of Immunoglobulin G and Improves Antioxidative Capacity, Immunity, and Intestinal Microbiota in Neonatal Goats - Yang, Chao; Zhang, Tianxi; Tian, Quanhua; Cheng, Yan; Gebeyew, Kefyalew; Liu, Guowei; Tan, Zhiliang; He, Zhixiong (Frontiers in Microbiology, 2022)
Successful establishment of passive immunity and regulation of intestinal microbiota are crucial for ruminants to maintain the intestinal health during the neonatal period. Thus, the objective of this study was to investigate the effects of mannan oligosaccharide (MOS) supplementation on passive transfer of immunoglobulin G (IgG), serum inflammatory cytokines and antioxidant levels as well as bacteria composition in the ileal digesta. A total of 14 healthy neonatal Ganxi black goats with similar birth weight (BW: 2.35 ± 0.55 kg) were selected and allocated into two groups, only fed colostrum and milk replacer (CON, n=7) and supplemented MOS (0.06% of birth BW) in the colostrum and milk replacer (MOS, n=7). The results indicated that MOS supplementation significantly reduced (P < 0.05) serum IgG level at 3 and 6 h after colostrum feeding. Goats in the MOS group had higher serum CAT and lower MDA level than those in the CON group (P < 0.05). Serum interleukin 4 (IL-4) level was increased (P < 0.05) while IL-6 level was reduced (P < 0.05) in the MOS group when compared with the CON group. In addition, MOS supplementation remarkably increased (P < 0.05) the level of secretory IgA in the ileal digesta. Principal coordinate analysis of 16S rDNA sequence of ileal microbiota showed that a distinct microbial differentiation between the CON and MOS groups (P < 0.05). The relative abundance of Firmicutes in the MOS group was higher than that in the CON group while the abundance of Verrucomicrobia was lower in the MOS group than that in the CON group at the phylum level (P < 0.05). The results of LEfSe analysis showed that MOS group was characterized by a higher relative abundance of Lactobacillus while the CON group was represented by a higher relative abundance of Akkermansia and Ruminiclostridium_5. Our findings demonstrated that MOS supplementation during the neonatal period increases antioxidant capacity and reduces the inflammatory response, and promotes IgA secretion and Lactobacillus colonization in the ileum, that indicates MOS supplementation might be an effective approach to maintain intestinal health and improve the surviving rate of neonatal ruminants.